Study of the types Glandular Trichomes and Eglandular of Sage (Salvia oﬃcinalis L.) - Bekbashy, Nabil Khalil; Haddad, Dina Ali; Moualla, Nizar Ali (Journal of agricultural, environmental and veterinary sciences, 2022)
This research studies the different patterns of the glandular and non-glandular trichomes of the species (Salvia officinalis L.) on the various vegetative and reproductive parts of the plant. The results confirmed the existence of two types: The first is non-glandular conical unbranched trichomes, either unicellular or multicellular. The second is glandular trichomes of two types, Peltate and Capitate. The peltate trichomes are of one shape and consist of a stalk, secretory cavity, and the oil-secreting cells whose number is (8-12 cells) that go through three stages during the life of the plant and differ in properties of morphology in terms of stalk length and secretory cavity size. The capitate glandular trichomes are consisting of a head, stalk, and neck cell, and they are classified according to the shape of the Head cell into four shapes, The First is a spherical unicellular or bicellular head. The second is of a small, oblong-shaped secretory head. The third one has a cup-shaped head but we also noticed a head that resembles a funnel none of the previous studies referred to it. The fourth form has a spherical head similar to the first shape, but differs from it by containing a hole from the top through which the secreted substances are released.
Keywords: Salvia Officinalis; Glandular Trichomes; Eglandular Trichomes; Peltate Trichomes; Capitate Trichomes